107k views
4 votes
Can someone show me step by step how to do this?

Can someone show me step by step how to do this?-example-1
User Ludell
by
6.7k points

1 Answer

1 vote


\bf \cfrac{2}{3}(x-4)(x+5)=1\implies \cfrac{2(x-4)(x+5)}{3}=1\implies \stackrel{\textit{cross-multiplying}}{2(x-4)(x+5)=3} \\\\\\ 2(\stackrel{\mathbb{FOIL}}{x^2+x-20})=3\implies \stackrel{\textit{distributing}}{2x^2+2x-40}=3\implies \underset{\textit{standard form}}{\stackrel{\stackrel{a}{\downarrow }}{2}x^2\stackrel{\stackrel{b}{\downarrow }}{+2}x\stackrel{\stackrel{c}{\downarrow }}{-43}=0}


notice, that'd be the standard form for a quadratic equation, all variables on the left-hand-side, sorted in ascending order.

User Grmihel
by
5.8k points